5m-7=-(m+5)-5

Simple and best practice solution for 5m-7=-(m+5)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m-7=-(m+5)-5 equation:



5m-7=-(m+5)-5
We move all terms to the left:
5m-7-(-(m+5)-5)=0
We calculate terms in parentheses: -(-(m+5)-5), so:
-(m+5)-5
We get rid of parentheses
-m-5-5
We add all the numbers together, and all the variables
-1m-10
Back to the equation:
-(-1m-10)
We get rid of parentheses
5m+1m+10-7=0
We add all the numbers together, and all the variables
6m+3=0
We move all terms containing m to the left, all other terms to the right
6m=-3
m=-3/6
m=-1/2

See similar equations:

| 6n–7n–=4+n | | 3(-6-5x)=-3-3(3x+1) | | 3(-6-5x)=-3-3(3x+1 | | 4x+3=7;x= | | 3x+-5=2x+1 | | X+7=-x+10 | | -8b-8(4b-3)=-6(6b+4) | | 3m/2/5m=2/3 | | 3t+11=8t-9 | | 7x^2+224=-84x | | y=3+60 | | 4(x-4)+8(4x+2)=36 | | y=3+42 | | 8a-22=5a-7 | | y=3+36 | | -4=-4x=12 | | y=3+30 | | 7x^2-5=51 | | -72=6(-3+8x)-3(-8+3x) | | y=21-12 | | 13p+85=2p+96 | | y=21-10 | | (2x–3)+(5x–6)=180 | | 19b+90=15b+98 | | y=21-8 | | (2y–3)+(5y–6)=180 | | 2(2x+4)=-18 | | y=21-6 | | 36=-(n-3)+3(n+7) | | 6a-4=4a+12 | | 5x+610x=31,1 | | 2s+8=4s-70 |

Equations solver categories